Picosecond acoustics in single quantum wells of cubic GaN/(Al,Ga)N - Czerniuk, T.; Ehrlich, T.; Wecker, T.; As, D.J.; Yakovlev, D.R.; Akimov, A.V.; Bayer, M. (American Physical Society, 2017)
A picosecond acoustic pulse is used to study the photoelastic interaction in single zinc-blende GaN/AlxGa1−xN quantum wells. We use an optical time-resolved pump-probe setup and demonstrate that tuning the photon energy to the quantum well’s lowest electron-hole transition makes the experiment sensitive to the quantum well only. Because of the small width, its temporal and spatial resolution allows us to track the few-picosecond-long transit of the acoustic pulse. We further deploy a model to analyze the unknown photoelastic coupling strength of the quantum well for different photon energies and find good agreement with the experiments.